Failure mechanism of LiNi0.6Co0.2Mn0.2O2 cathodes in aqueous/non-aqueous hybrid electrolyte. Issue 7 (31st January 2023) - Du, Leilei; Hou, Xu; Berghus, Debbie; Frankenstein, Lars; Schmuch, Richard; Wang, Jun; Paillard, Elie; Winter, Martin; Placke, Tobias; Li, Jie
Abstract : Based on the LiNi0.6 Co0.2 Mn0.2 O2 cathode (NCM622), this work confirmed the occurrence of H + intercalation upon charging in hybrid electrolyte, which is dramatically severe at high de-lithiated states. Abstract : The urgent need for improving the energy density of aqueous lithium ion batteries (ALIBs) can be addressed by the implementation of advanced electrode materials and electrolytes. The utilization of layered oxide cathodes, particularly Li[Ni x Co y Mn z ]O2 (NCM) materials, is an effective strategy, as they can offer high specific capacities in an appropriate voltage range. However, due to the strong effect of humidity on the degradation of Ni-rich layered oxide cathodes, using these materials together with highly concentrated aqueous electrolytes is critical. In this work, the underlying mechanisms responsible for the degradation of Li[Ni0.6 Co0.2 Mn0.2 ]O2 (NCM622)‖TiO2 @LiTi2 (PO4 )3 (P/N = 1.2 : 1) full-cells are systematically explored by comprehensive studies, involving the evolution of the lattice structure of NCM622 and electrochemical impedance dependent on the operating voltage range (0.7–2.8 V or 0.7–2.9 V). It is found that in aqueous/non-aqueous hybrid electrolyte, in addition to the discharge process, proton intercalation into NCM622 also takes place during the charging process, which is dramatically severe at higher upper cut-off voltage (2.9 V), leading to a rapid degradation of the cathode material. The intercalated protons not only aggravate the electrochemical impedance by blocking Li + diffusion, but also activate the higher potential redox pairs. This experimental study offers an in-depth understanding about the failure mechanism of NCM622 cathode materials in aqueous electrolytes.